2019
DOI: 10.1186/s12889-019-7053-1
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent girls’ health, nutrition and wellbeing in rural eastern India: a descriptive, cross-sectional community-based study

Abstract: Background India is home to 243 million adolescents. Two million (9%) of them belong to Scheduled Tribes living in underserved, rural areas. Few studies have examined the health of tribal adolescents. We conducted a cross-sectional survey to assess the health, nutrition and wellbeing of adolescent girls in rural Jharkhand, eastern India, a state where 26% of the population is from Scheduled Tribes. We aimed to identify priorities for community interventions to serve adolescents and their families.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 24 publications
5
32
1
Order By: Relevance
“…AWC's has an important role in creating health-related awareness and nutritional status in community. In current study, 59% were undernourished which is comparable to study by IIPHG[14] (60%), Rose –Clarke[13] (41%), and higher than NFHS 4 (22.9%). [15] Study finding indicated that there were poor knowledge, unfavorable attitude, and satisfactory practice about iron deficiency anemia among study participants.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…AWC's has an important role in creating health-related awareness and nutritional status in community. In current study, 59% were undernourished which is comparable to study by IIPHG[14] (60%), Rose –Clarke[13] (41%), and higher than NFHS 4 (22.9%). [15] Study finding indicated that there were poor knowledge, unfavorable attitude, and satisfactory practice about iron deficiency anemia among study participants.…”
Section: Discussionsupporting
confidence: 83%
“…[1112] A study from the tribal area reported much higher dropout of 23%. [13] All of the AGs were aware of Anganwadi center and its location but few were aware of services provided for them. AGs believe the AWC to be only limited to preschool children.…”
Section: Discussionmentioning
confidence: 99%
“…In eastern India in particular, there was discrepancy between planned and actual coverage. Our baseline survey of 3324 girls aged 10-19 years in 50 villages in Jharkhand provided additional formative data [21]. We found substantial school drop-out after the age of 15: less than half of girls aged 15-19 were still in school.…”
Section: Formative Research To Develop a Community Adolescent Health mentioning
confidence: 85%
“…One-third of the population are below the age of 15 [23]. Eighteen percent of adolescent girls aged 10-19 cannot read, and a further 30% read with difficulty [21]. More than one-fifth of girls aged 15-19 are married [21].…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation